ANALYSIS OF THE INFLUENCE OF ASIAN STOCK EXCHANGES ON THE COMPOSITE STOCK PRICE INDEX DURING THE COVID-19 PANDEMIC IN 2021 IN THE INDONESIAN CAPITAL MARKET - Hasanudin (SEAN Institute, 2022)
This study aims to determine the influence of the Asian Stock Price Index consisting of the Shenzhen Index (China), KOSPI Index (South Korea), Hang Seng Index (Hong Kong), and Nikkei 225 Index (Japan) on the Composite Stock Price Index in Capital Markets 2021 with Metode This research uses the ARCH (Autoregressive Conditional Heteroskedasticity) / GARCH analysis method (Generalized Autoregressive Conditional Heteroskedasticity). In December 2019, China announced the first case of the Covid-19 virus which could potentially be a pandemic in a country. This is because the spread of this virus very quickly through the air and then into human breathing. So that causes many sectors in countries that experience declines such as economic sectors, especially capital markets in Indonesia. The data in the study was analyzed using the Eviews version 9 computer program. The results of this study showed that the Shenzhen Index had a significant negative effect on JCI, the KOSPI Index had an insignificant positive effect on JCI, the Hang Seng Index had an insignificant positive effect on JCI, and the Nikkei 225 Index had a significant negative effect on JCI.